THE EFFECT OF CAPITAL INTENSITY RATIO, RETURN ON ASSET, AND FIRM SIZE ON TAX AGRESSIVINESS - Wahyu Ferawati, Indah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This research aims to analyze the effect of capital intensity ratio, return on asset, and firm size on tax agressiviness. The sample of this research are property and real estate companies which listed in Indonesian Stock Exchange period 2017-2019. The method which used in this research is purposive sampling and multiple linear regression analysis to analyze data and supported by SPSS version 2.2. The result of this research show simustaneously the capital intensity ratio, return on asset, and firm size on tax agressiviness. While partially show the caapital intesity ratio and return on asset has influence on tax agressiviness. Firm size doesn’t have an influence on tax agressiviness. For the result of coefficient determination testing (R2) show the value 0,231, which mean that 23,1% has influence by independent variable and the rest influenced by another factors.